Employee Assessment Applications Using the Graphic Rating Scale and Profile Matching Methods at XYZ University - Kukuh Ujianto; Indra Gita Anugrah (Journal of Development Research, 2021)
Performance appraisal is an evaluation and assessment carried out to employees to find out what their abilities are and measure productivity during work. XYZ University has an employee performance appraisal which is conducted annually to determine employee promotions. The assessment process is still using the manual method and using the Graphic Rating Scale method. Graphic Rating Scale is a performance appraisal method in which an employee is assessed based on criteria that are considered important and relevant to performance and productivity. To determine a promotion, the Graphic Rating Scale method cannot do it because it takes standard values, core factors and secondary factors that are used as standards to determine promotions. Therefore, In this employee appraisal application there is a combined method used to assist the assessment process, namely the Graphic Rating Scale method and the Profile Matching method. The Profile Matching method is used because there are standard values, core factors and secondary factors that can be used as standards to determine promotions. The results of this study are on testing the Graphic Rating Scale method with the combined method of Graphic Rating Scale and Profile Matching, the combined method of Graphic Rating Scale and Profile Matching has a higher average accuracy of 78,18%, while the Graphic Rating Scale method has an average accuracy of 68,45%.